Numerical doubly-periodic solution of the (2+1)-dimensional Boussinesq equation with initial conditions by the variational iteration method - İnç, Mustafa (Elsevier, 2007)
In this Letter, a scheme is developed to study numerical doubly-periodic solutions of the (2 + 1)-dimensional Boussinesq equation with initial condition by the variational iteration method. As a result, the approximate and exact doubly-periodic solutions are obtained. For different modulus m, comparison between the approximate solution and the exact solution is made graphically, revealing that the variational iteration method is a powerful and effective tool to non-linear problems. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: (2+1)-dimensional Boussinesq equation; variational iteration method; Lagrange multiplier